Selective localization of multi-walled CNT in polylactic acid /thermoplastic polyurethane blends and its effect on mechanical properties - Buys, Yose Fachmi; Mawardi, Munirah Afiqah; Anuar, Hazleen (Bentham Science, 2018)
Due to excellent properties such as degradability, high strength, and bio-compatibility, polylactic acid (PLA) has received enormous attention recently as a promising potential candidate material to replace petroleum-based polymers. However, PLA shows high brittleness as well as low toughness which may limit its application. In this work, PLA was melt blended with thermoplastic polyurethane (TPU) and then filled with carbon nanotubes (CNTs) to produce environmentally friendly polymeric materials with improved mechanical properties. Observation from Scanning Electron Microscopy’s micrograph showed that two distinct phases were present in the blend, with selective localization of CNTs at one of the phases in the system. Thermodynamic calculation using Owen and Wendt’s equation predicted that the CNTs were preferably dispersed at TPU phase. As CNTs content increased, the toughness of TPU/CNT and TPU/PLA/CNT composites increased whereas the toughness of PLA/CNT composite decreased, that might be ascribed to the phenomenon of selective localization of the CNTs. Other than that, the elongation at break of PLA/CNT, PLA/TPU/CNT and TPU/CNT also increased with the addition of CNT. The incorporation of TPU in the TPU/PLA blends also imparted ductility to the blends.